HUBUNGAN KANDUNGAN NITRAT DAN FOSFAT DENGAN KELIMPAHAN DIATOM DI PERAIRAN PANTAI PANIPAHAN KABUPATEN ROKAN HILIR PROVINSI RIAU - Yuke Constina; Bintal Amin; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT               This study was conducted in April 2017 by taking samples from four stations with three replications in each sampling station. The resultsof the study revealed that the highest nitrate concentrations in waters was 0,457 ± 0,2571 mg/L in Station 2, while the lowest nitrate concentration was 0,206 ± 0,0115 mg/L inStation 4. The most common planktonic diatoms species found were Isthmia sp and Hemialus sp. Linear regression analysis showed that the relationships of nitrate and  phosphate concentrations with diatom abundance  is shown as Y = 4744,7 + 5080,8x (R² = 0,1094; r = 0,330) and Y = 4767,2 + 9343x (R² = 0,0611 and r = 0,2471). Judging from the r value of those equation, the coastal waters of Panipahan can be categorized as having moderate (Nitrate) and weak (phosphate) fertility, respectively.  Keywords: Nitrate, Phosphate, Diatom Abundance, Panipahan Coastal Waters